(untitled) (Al-Academy, 2022)
The current research dealt with the development of sciences and arts over the course of human history, and the development of sciences with their natural and human trends are important areas in developing the knowledge and application base for industrial product design and design in its various fields. Bionic science is one of the sciences that works on applying biological methods and systems found in nature to study and design engineering systems and modern technology, and for industrial products to be highly efficient, durable and resistant to natural variables in daily life for use. The transfer of technology between life forms and industrial products is desirable because the processes of development at the level of science in general and the development of human needs in particular impose on the design of industrial products to be compatible with human changes and transformations at various levels, and therefore the process of adopting the scientific base of bionic science It is essential for the development of industrial products In proportion to the requirements of the contemporary user, the research dealt with the mechanisms of applying bionic science in industrial products, as the theoretical framework included three important topics, which we will address successively